2016
DOI: 10.1108/whatt-02-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic portrait of Russian travelers

Abstract: Purpose Focuses on the social and demographic features of inbound and outbound Russian travelers, in particular, on target groups of travelers and the challenges they face in Russia. Design/methodology/approach Draws on analysis of Synovate Comcon Russian Target Group Index and TNS Marketing Index databases, Rosstat data, expert round table discussion with author participation and observation and interviews in tourist-related sites during 2014-2015. Findings The most important factors for domestic tourism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…• Tambovtsev (2016) attempted to reveal institutional restrains impeding tourism development and to create a theoretical basis for institutional WHATT 8,3 development that could provide positive tourist experience production in emerging markets; • Kalabikhina and Shishalov (2016) examined more precisely the socio-demographic portrait of Russians engaged in travelling both in Russia and abroad; • Kazakov (2016) shed light on the market orientation concept and the implementation influence on company business performance in a local service industry on emerging market; • the articles by Sheresheva et al (2016) and Oyner and Korelina (2016) are focused on Russian hospitality challenges and opportunities in more complicated environments, examining the general market situation, the strategy of international and local operators and new forms of customer engagement in value co-creation, leading to better customer satisfaction; • the articles by Aleksandrova and Vladimirov (2016) and Polukhina (2016) are dedicated to the problems associated with boosting tourism cluster development and network interaction in Russian regions, including requirements for state support of cluster initiatives in the field of tourism. A number of cases are provided to illustrate and analyze perspectives of clustering and networking in the Russian hospitality and tourism market; and • finally, Merzlov and Karpov (2016) present a case of the association of the most beautiful villages of Russia and assess the experience economy approach as a base for successful association development.…”
Section: Success Factorsmentioning
confidence: 99%
“…• Tambovtsev (2016) attempted to reveal institutional restrains impeding tourism development and to create a theoretical basis for institutional WHATT 8,3 development that could provide positive tourist experience production in emerging markets; • Kalabikhina and Shishalov (2016) examined more precisely the socio-demographic portrait of Russians engaged in travelling both in Russia and abroad; • Kazakov (2016) shed light on the market orientation concept and the implementation influence on company business performance in a local service industry on emerging market; • the articles by Sheresheva et al (2016) and Oyner and Korelina (2016) are focused on Russian hospitality challenges and opportunities in more complicated environments, examining the general market situation, the strategy of international and local operators and new forms of customer engagement in value co-creation, leading to better customer satisfaction; • the articles by Aleksandrova and Vladimirov (2016) and Polukhina (2016) are dedicated to the problems associated with boosting tourism cluster development and network interaction in Russian regions, including requirements for state support of cluster initiatives in the field of tourism. A number of cases are provided to illustrate and analyze perspectives of clustering and networking in the Russian hospitality and tourism market; and • finally, Merzlov and Karpov (2016) present a case of the association of the most beautiful villages of Russia and assess the experience economy approach as a base for successful association development.…”
Section: Success Factorsmentioning
confidence: 99%
“…First, except for marital status and having children in the household, there were no statistically significant differences in the demographic characteristics among business, pleasure, and VFR travelers who participated in this study. Although some demographic characteristics such as family status, employment, income and education were linked in previous research to travel behavior (Aziz et al , 2018; Kalabikhina and Shishalov, 2016), these studies were conducted before the COVID-19 pandemic. We can conclude that during chaotic times, demographic characteristics may not be significant predictors of travel activity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies looked at the sociodemographics of certain traveler segments such as business, pleasure and VFR travelers. For example, Kalabikhina and Shishalov (2016) found that the most important predictors for Russian domestic tourism were family status, employment, income and education. The most important factors affecting Russian tourists' outbound international travel were their region of residence, the size of their city and income status.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies found that religious tourists’ motivation can be influenced by three other factors: socio-demographic characteristics, satisfaction, and loyalty. First, tourism socio-demographic aspects of are tourists’ properties or attributes of such as gender, age, educational level, job, income, region, and nationality [ 3 , 10 ]. It is crucial to study those aspects because of their role in explaining the differences in tourists’ lifestyles and travel motivations hand and their impact on the tourists’ demand and tourism services [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, tourism socio-demographic aspects of are tourists’ properties or attributes of such as gender, age, educational level, job, income, region, and nationality [ 3 , 10 ]. It is crucial to study those aspects because of their role in explaining the differences in tourists’ lifestyles and travel motivations hand and their impact on the tourists’ demand and tourism services [ 10 12 ]. The socio-demographic characteristics of tourists were also found to have a significant impact on families’ travel plan, behaviour, and expenditures [ 13 ].…”
Section: Introductionmentioning
confidence: 99%